A Comparison of NoSQL and Relational Database Management Systems (RDBMS) - B.M. Rajesh; Divya Bharathi C.; Pavithra R. (International Journal of Data Structure Studies, 2023)
The new aspirant is a non-relational abstracts abundance which is widely deployed in large website environments where there is less reliance on relational databases, leading to enhanced performance in the field of data retrieval. NoSQL are additionally accepted as non-relational databases adulation relational databases and are now acclimated by the world's bigger organizations such as Facebook, Amazon, and Google. Both models are acceptable in specific areas and for specific applications. Depending on what issues are to be apparent by the company, it will actuate the best of a database archetypal to be adopted. Some organizations, however, adopt to accomplish use of an amalgam database which is the aggregate of both NoSQL and relational databases contrarily referred to as multimodel database. The aspect of this cardboard is to emphasize the importance this almost new technology and acutely appearance its architecture. NOSQL aegis appearance will be compared with the better-known relational databases for bigger understanding. This analysis will accredit affluence of best for those who accept the charge for such databases or facilitate the best to embrace the trending convenance of combining both in the same application to create a hybrid database.
Keywords: BLOB; Database; JSON; SQL; XML